Interaction between ministers and members of the Congregations in the DRCA FS (NGKA VS) - Pali, K. J. (Scriptura, 2020)
Recent studies on the DRCA FS indicate that there is a decrease in the positive interaction between ministers and the members of their congregations. This is manifested in the way in which the ministers describe the members of their congregations or the way in which congregation members describe the leadership of their ministers. This decrease in interaction between ministers and the members of their congregations is reflected in the increase in conflict situations characterised by disagreements, litigations and violence. This article raises the following research question: What are the dynamics of the interaction between ministers and members of the congregations in the DRCA FS? This article aims to analyse the interaction between ministers and members of the congregations in the DRCA FS.